Rwanda : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion and Modification of Performance Criteria; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2008)
This paper discusses key findings of the Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) for Rwanda. All but one of the end-2007 quantitative performance criteria were met. IMF staff supports the authorities' request for a waiver of the nonobservance of the performance criterion on net credit to government. IMF staff also recommends completion of the Fourth Review under the PRGF arrangement based on Rwanda's performance and understandings reached on the macroeconomic and structural program for 2008.